Development of Sharia Hospitals as a Source of New Economic Growth - Wahyu Sulistiadi; Dumilah Ayuningtyas; Vetty Yulianty Permanasari; Prasetyaning Jati; Ira Gustina; Nisrina Widyasanti (Journal of Islamic Monetary Economics and Finance, 2025)
The development of Sharia hospitals represents a unique integration of Islamic values into healthcare services, fostering new avenues for economic growth. This study has three key objectives: (1) examining factors contributing to the establishment of Sharia hospitals, (2) analyzing the essential elements of Sharia hospital development using the Business Model Canvas (BMC) to ensure sustainability; and (3) assessing Sharia hospitals' potential to drive economic growth. Through a mixed-methods approach, quantitative data were collected from 619 patients and 149 respondents, while qualitative insights were gathered through focus group discussions and in-depth interviews with stakeholders including hospital managers and policymakers. Results indicate that Sharia hospitals report higher levels of patient satisfaction and loyalty compared to non-sharia hospitals, with significant emphasis on service quality, and experiential marketing. The integration of Islamic financial instruments such as Zakat, Infak, Sedekah, and Wakaf (ZISWAF) also enhances financial accessibility for underserved populations, promoting equitable healthcare. Indonesia also has the opportunity to open up Muslim-friendly health tourism destinations, attracting patients from other Muslim-majority countries. The growth of Sharia hospitals also contributes to the expansion of the halal ecosystem in Indonesia. This is not only beneficial for the health sector but also drives economic growth. Acknowledgment The authors acknowledge the support from the Research Grant Bank Indonesia (RGBI) 2024, for funding this research endeavor.